Protein zero Gene expression is regulated by the glial transcription factor Sox10 - Wegner, Michael; et al. (Molecular and Cellular Biology, 2000)
Myelinating glia express high levels of a unique set of genes which code for structural proteins of the myelin sheath. Few transcription factors have so far been implicated in the regulation of any myelin gene. Here we show that the protein zero (P0) gene, a myelin gene exclusively expressed in the Schwann cell lineage of the peripheral nervous system, is controlled in its expression by the high-mobility-group domain protein Sox10 both in tissue culture and in vivo. Induction of wild-type Sox10, but not of other transcription factors or Sox10 mutants, strongly increased endogenous P0 expression in tissue culture. This activation was mediated by the P0 promoter, which was stimulated by Sox10 in transient transfections. Detailed analyses revealed the involvement of a proximal and a distal promoter region. The distal region functioned only in conjunction with the proximal one and contained a single Sox consensus binding site, which accounted for most of its activity. In contrast, the proximal region mediated Sox10 responsiveness on its own. It contained multiple binding sites for Sox proteins, with two high-affinity sites being the most significant. P0 expression also depended on Sox10 in vivo, as evident from the analysis of Schwann cell precursors in mouse embryos with Sox10 mutation at day 12.5 of embryogenesis. To our knowledge this is the most conclusive link to date between a glial transcription factor and cell-specific activation of myelin gene expression.
UnivIS-Import:2015-03-05:Pub.2000.med.IB.LPCIPDBI.protei